Approximation of functions by linear methods in weighted Orlicz type spaces with variable exponent - S.O. Chaichenko; A.L. Shidlich (Researches in Mathematics)
The approximation properties of various classical methods of linear summation of Fourier series in weighted spaces of Orlicz type with variable exponent are considered. In particular, in terms of approximation by such methods the constructive characterizations for classes of functions whose moduli of smoothness do not exceed some majorant are obtained.